Pengaruh Tingkat Suku Bunga, Volume Perdangan dan Nilai Tukar Terhadap Return Saham Sektor Properti - Triana Sri Gunarti (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
This study aims to assess macro-economic indicators to assess securities, SBI interest rates, exchange rates and trading volumes in the property sector of stock returns during the 2013-2017 period. Data obtained from the JSX Statistics, ICMD (Indonesian Capital Market Directory) and Bank Indonesia (BI) with monthly time periods from January 2013 to December 2017. The population in thisstudy were 20 companies with purposive sampling transfer phase. The analysis technique used in this study is multiple linear regression. The results show that the exchange rate variable has a partial negative and significant effect, while the variable interest rates and trading volume have a positive and significant impact on stock returns. Independent variables together have a significant effect on the dependent variable.